MORTALITAS PREVALENSI DAN INTENSITAS TELUR CACING PARASIT PADA KUKU SISWA SEKOLAH DASAR DI SDN 007 KELURAHAN BUGIS DAN SDN 007 KELURAHAN SUNGAI PINANG LUAR KECAMATAN SAMARINDA KOTA - Meilinda, Fanellya; Hariani, NOva; Sudiastuti2, Sudiastuti (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Worm infections are one of the common diseases that spread around the world. Media transmission is divided into two groups, namely the group of worms STH (Soil Transmitted Helminths) and the group of worms Non-STH (Soil Transmitted Helminths). The parasite entry into the body is divided into three way hand to mouth, vector (Intermediate hospes), and hospes definitive. The aim of this research is to know the prevalence and intensity of parasitic worm eggs, the difference of the number and types of parasitic worm eggs on the students' nails at Elementary School 007 in Bugis village and Elementary School in Sungai Pinang Luar village. This research method uses descriptive quantitative and sampling technique using purposive sampling method. The Data collection in the field conducted interviews and cutting student nail samples. For sample analysis techniques used two methods namely floating method and sedimentation method. The results showed that the type and number of the highest eggs were found on the students' nails at Elementary School 007 in Bugis village and Elementary School 007 in Sungai Pinang Luar village, are the same type of egg Ascaris lumbricoides, while the fewest are Oxyuris vermicularis. Prevalence and intensity on student's nail at Elementary School 007 in Bugis village is 100% and its intensity is 12,25 grains/ind., while on the student’s nail at Elementary School 007 in Sungai Pinang Luar village that dominates is 100% and its intensity is 20.8 grains/ind.